Development and Application of Releasable Cable Head in 10 000 m Ultra Deep Well - ZHANG Haijun; ZHANG Bingjun; SUN Jianwei; MA Jianghu; XU Rui; WANG Kun; GUO Shuai; CHEN Jisheng (Cejing jishu)
The exploration and development of ten thousand meter ultra deep oil and gas is a key strategic direction for oilfield companies to search for large oil and gas fields, develop oil and gas storage and increase production in the future. In response to the problems of high temperature and high pressure, complex well conditions, and weak cable settings in ultra deep well cable logging, the mechanical structure and electrical control release device of the cable head are studied, and a circuit insulation bottle is matched to form a 260℃/210 MPa releasing cable head for ten thousand meter ultra deep wells. To verify its performance, mechanical force analysis of the outer shell of the upper and lower joint components of the cable head, temperature resistance test of the release circuit, ground release test of the electronic control release device, and online release test of the overall high temperature and high pressure kettle of the cable head are carried out in sequence, and multiple onsite applications are carried out. The results show that the cable head has good temperature and pressure resistance performance, and the electric control release device is stable and reliable, which has the value of promotion and application.